Central ellipsoid of inertia in analyzing snowboard trick flight - single and double "wildcat" - case study - Bacik, B.; Kurpas, W.; Starzynski, M.; Sobota, G.; Juras, G. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: Here we present the potential of central ellipsoid of inertia model which provides dimensionally reduced description of complex human motion. Methods: The subject of this study was a single 26 years old male competitor who has been training snowboard since 2002 (body high 174 cm, body mass 65 kg). He performed 10 snowboard "wildcat" backflip tricks (4 single and 2 double) in a controlled environment. The ramp used was 5.6m high and 16.6m long; the 2.3 drop was angled at 30 degrees. We used Motion Capture Vicon system consisting of 10 cameras (4MP resolution, acquisition speed 100Hz). We used human body model based on Vicon Nexus software and Plug-in Gait model. The cameras were mounted on special crate placed 2m above the ramp drop. The measured space was an elliptical cylinder of height 3m and base axis of lengths 6.47m and 4.20m. Results: Mean height of center of mass (CoM) was similar in single (1.92 m SD 0.2 m) and double backflips (2.06 m SD 0.05 m). Likewise, CoM velocities 1m above the ramp were also similar for vertical (single 3.57 m/s SD 0,61 m/s and double backflips 3.75 m/s SD 0,35 m/s) and horizontal component (single 4.95 m/s SD 0.35 m/s and double backflips 5,00 SD 0,28 m/s). However, cumulative moment of inertia as well as flight time were different in the two types of backflips. Conclusion: Central ellipsoid of inertia model can be useful in analysing sport techniques, particularly for complex aerial movements, where CoM describe only resultant body motion.